Sistem Informasi Inventarisasi Sumberdaya Perikanan Kabupaten Maluku Tenggara Dengan Metode Rapid Application Development Berbasis Web - Lidya Elsye Reniban (JURNAL TEKNIK KOMPUTER, 2019)
- Southeast Moluccas Regency is a districts in Moluccas Province that  is  rich in marine fisheries resources, especially pelagic fish, seaweed, and demersal fish. Knowledge of information fisheries resources by fishermen and the community in general in the regions is still low, because the unavailability of easy information media  to access information about  fisheries resources in this area. The research aims to design an information system of  fisheries resources inventory to improve the performance of the Southeast Moluccas Regency Government to inform and process data on  fisheries resources. System design method uses RAD (Rapid Application Development). System design tools use UML (Unified Modeling Language), to make applications using the PHP(Hypertext Preprocessor) programming language, and MySQL as the database. Information System for Fisheries Resources  has been tested using the blackbox method, the results show the  system runs as expected. This system can display information on Southeast Moluccas Regency  Fisheries Resources informally to the public and  can be used as a tool for local governments to improve performance for presentation and  processing of data and information in the  marine  and fisheries sector.  Keywords: Information Systems,Inventory,  Fisheries, RAD, UML